Efektivitas Program Keluarga Harapan (PKH) Terhadap Kesejahteraan Masyarakat Studi Kasus Kelurahan Oesapa Barat Kecamatan Kelapa Lima Kota Kupang - Nappu, Putri Indriani Gracela (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the impact of the Family Hope Program (PKH) on community welfare in Oesapa Barat Village, Kelapa Lima District, Kupang City. PKH is a conditional cash transfer program implemented by the Indonesian government to improv the quality of life of low-income families through education, health, and social welfare support. This study used a qualitative research approach, with data collected through observation, interviews, and documentation. Informants included the Village Head of Oesapa Barat, PKH facilitators, beneficiary families, and community members who had not yet received PKH assistance. Data were analyzed using qualitative data analysis techniques, including data reduction, data presentation, and conclusion drawing. The findings indicate that the Family Hope Program has a positive impact on community welfare. In the education sector, PKH assistance helps families meet their children’s educational needs and supports school participation. In the health sector, the program facilitates access to essential health services. Furthermore, in terms of social welfare, the Family Hope Program (PKH) helps reduce the economic burden on beneficiary families and contributes to an overall improvement in their standard of living. However, several challenges remain, including inaccurate beneficiary data, limited public understanding of the program, and dissatisfaction among non-beneficiaries. Therefore, stronger coordination among stakeholders and more effective program outreach are needed to improve the implementation and effectiveness of the Family Hope Program (PKH) in the future.